Variety of Cyber Counseling Media During the Covid-19 Pandemic - Dilla Astarini; Hermi Pasmawati (JURNAL ILMIAH SYI'AR, 2021)
This paper describes cyber Counseling that counselors can use in carrying out Guidance and Counseling Services during the Covid-19 pandemic. The recommended service focus is using Cybercounseling with the website, youtube, social media, and google from platforms. Advances in technology and the occurrence of the Covid-19 pandemic situation require Counselors to have the ability to apply Cybercounseling. The research method used is a literature study method, examining relevant references in collaboration and relevance with various services and supporting activities in Guidance and Counseling. The relevant platforms are used to implement services and support activities based on various existing references. The website platform can provide information services, individual Counseling, and consultations. The youtube platform can carry out information services, whether made by the Counsellor himself or information from other people's youtube content. The social media platform can provide information services, individual Counseling, consultation, group counseling, and share essential links with service stakeholders. The google form platform can carry out supporting activities and data collection. By analyzing the effectiveness of the services used by the demands of the times, the Counsellor should be able to apply the cybercounseling application. This research will be more comprehensive if the effectiveness of each use of cyber Counseling is evaluated in implementing Guidance and Counseling support services and activities.